Expression and Characterization of a Thermostable Carrageenase From an Antarctic Polaribacter sp. NJDZ03 Strain - Gui, Yuanyuan; Gu, Xiaoqian; Fu, Liping; Zhang, Qian; Zhang, Peiyu; Li, Jiang (Frontiers in Microbiology, 2021)
The complete genome of Polaribacter sp. NJDZ03, which was isolated from the surface of Antarctic macroalgae, was analyzed by next-generation sequencing, and a putative carrageenase gene Car3206 was obtained. Car3206 was cloned and expressed in Escherichia coli BL21(DE3). After purification by Ni-NTA chromatography, the recombinant Car3206 protein was characterized and the antioxidant activity of the degraded product was investigated. The results showed that the recombinant plasmid pet-30a-car3206 was highly efficiently expressed in E. coli BL21(DE3). The purified recombinant Car3206 showed a single band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis, with an apparent molecular weight of 45 kDa. The optimum temperature of the recombinant Car3206 was 55 °C, and it maintain 60 % to 94 % of its initial activity for 4–12 h at 55 °C. It also kept almost 70 % of the initial activity at 30 °C, and more than 40 % of the initial activity at 10 °C. These results show that recombinant Car3206 had good low temperature resistance and thermal stability properties. The optimum pH of recombinant Car3206 was 7.0. Car3206 was activated by Na+, K+, and Ca2+, but was significantly inhibited by Cu2+ and Cr2+. Thin-layer chromatographic analysis indicated that Car3206 degraded carrageenan generating disaccharides as the only products. The antioxidant capacity of the degraded disaccharides in vitro was investigated and the results showed that different concentrations of the disaccharides had similar scavenging effects as vitamin C on O2•−, •OH, and DPPH•. To our knowledge, this is the first report about details of the biochemical characteristics of a carrageenase isolated from an Antarctic Polaribacter strain. The unique characteristics of Car3206, including its low temperature resistance, thermal stability, and product unity, suggest that this enzyme may be an interesting candidate for industrial processes.